(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2019)
University libraries provide an important service to society, contributing to spread knowledge and cultivating new talents in the academic environment. The main objective of this article is to perform a review of the literature on efficiency assessments in the context of university libraries. The databases Web of Science and Scopus were adopted as reference to search for papers in the aforementioned context and identify the methodologies used and perspectives set out by different authors. A complementary search was also made on Google Scholar to obtain additional articles. In sum, 34 papers were found to compose the core of analyzed publications. As result, we observed that nearly 90% of the papers use Data Envelopment Analysis to assess the efficiency of university libraries and other methodologies with the same proposal were identified. Moreover, the variables used in these publications were analyzed, contributing to the mapping of main inputs and outputs that directly affect the services of university libraries. Furthermore, other characteristics were also considered, such as: temporal placement of publications and countries with the largest production of papers. Finally, based on the results of this study, further researches are suggested. Keywords: Academic libraries. Evaluation methods. Bibliographical revision. Link: http://www.scielo.br/pdf/tinf/v30n1/2318-0889-tinf-30-1-0065.pdf